Integration of 3D interconnected porous microstructure and high electrochemical property for boron-doped diamond by facile strategy. (10th April 2022) - Lu, Zhigang; Huang, Nan; Zhai, Zhaofeng; Chen, Bin; Liu, Lusheng; Song, Haozhe; Yuan, Ziyao; Zhang, Chuyan; Yang, Bing; Jiang, Xin
Highlights: A new template-free approach for constructing porous BDD films is presented. Integration of high-quality diamond and unique 3D interconnected porous microstructure is achieved. 3D porous BDD film exhibits high electrochemical response, wide potential window and large double layer capacitance. Relationship between electrochemical behavior and microstructure is discussed. Abstract: Three-dimensional (3D) porous boron-doped diamond (BDD) film is an attractive electrode material but tough to synthesize. Herein, the 3D porous BDD films were constructed in a facile and template-free way. The BDD/non-diamond carbon (NDC) composite films were firstly fabricated by hot filament chemical vapor deposition (HFCVD) technique, and then the porous BDD films with 3D interconnected porous microstructure, different pore size and NDC-free diamond were achieved by selective removal of NDC. It is manifested that higher electrochemical response, large double layer capacitance (17.54 mF/cm 2 ) in diamond electrodes, wide electrochemical window of 2.6 V and superior long-term stability were achieved for 3D porous BDD film. This derives from the synergistic effect of microstructure and phase composition of the porous films. 3D interconnected structure possesses prominent improvement of effective surface area and accessible porous channel, significantly enhancing the species adsorption and mass transfer. The 3D porous BDD films, composed of NDC-free diamond, exhibit excellent structural stability and corrosion resistance, which favor the enhancement of long-term stability and water splitting overpotential. The facile fabricating approach and excellent structure/electrochemical character demonstrate the appealing application in many electrochemical fields for 3D porous BDD films, such as energy storage and conversion, wastewater treatment and purification. Graphical abstract: Image, graphical abstract The electrochemical performance of boron-doped diamond (BDD) film is improved significantly through constructing three-dimensional interconnected porous microstructure with high-quality diamond, which is synthesized facilely by deposition of BDD/non-diamond carbon (NDC) composite film and selectively removing NDC.